Targeted Intracellular Production of Reactive Oxygen Species by a 2D Molybdenum Disulfide Glycosheet - Ji, Ding-Kun; Zhang, Yue; Zang, Yi; Li, Jia; Chen, Guo-Rong; He, Xiao-Peng; Tian, He (Advanced materials (Weinheim), 2016)
A 2D “glycosheet” based on supramolecular self‐assembly between 2D MoS2 and fluorescent glycoligands is developed. The composite 2D material is proven suitable for targeted intracellular production of reactive oxygen species (singlet oxygen) by the sequential control of a receptor endocytosis and light irradiation.